ANALYSIS AND INTERVENTIONS OF COMMON SPORTS INJURIES IN COLLEGE BASKETBALL PLAYERS - Zhang,Ming (2023)
ABSTRACT Introduction As college basketball continues to develop, more and more college students are joining the sport, and the resulting sports injuries have also gradually increased, affecting the quality of life and academic performance. Objective Analyze the most common sports injuries and offer solutions for the safe practice of college basketball. Methods This article studies, through interviews and literature review, the basketball injuries of college students, analyze the main causes of sports injuries, and presents corresponding countermeasures to promote the safe development of sports education in colleges. Results The main injuries were during training, excessive force, and inadequate preparation. Deficient muscle work is also associated with most of these injuries. Conclusion Basketball is highly competitive and popular on college campuses. It is a sport that can exercise and enrich the extracurricular life of college students, requiring from its practitioners greater attention in the pre-training warm-up phase and parallel muscle strengthening to reduce its major injuries in college students. Level of evidence II; Therapeutic studies - investigation of treatment outcomes